Can Risk Averse Competitive Input Providers Serve Farmers Efficiently in Developing Countries? - Makdissi, Paul; Wodon, Quentin (2012)
Under price ceilings and quality floors for agricultural inputs in cash crop sectors in developing countries where credit markets are weak, imperfect information on the ability of farmers to pay for their inputs at the end of the cropping season may lead the decentralized production of those inputs by risk averse private input providers to be inefficient. A coordinating agency and/or subsidies for new farmers could help to produce and distribute more agricultural inputs, thereby increasing the profits for input providers while also enabling more farmers to produce the crops that are key to their livelihood.